2013
DOI: 10.1177/0047287513500393
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change, Discretionary Air Travel, and the “Flyers’ Dilemma”

Abstract: Abstract:The 'flyers' dilemma' describes the tension that now exists between the personal benefits of tourism and the climate concerns associated with high levels of personal aeromobility. This article presents the first international comparative analysis of attitudes towards climate change and discretionary air travel, providing insights into areas of convergence and divergence across three European societies -Norway, the United Kingdom and Germany. Employing a critical interpretive approach and drawing upon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 95 publications
(83 citation statements)
references
References 48 publications
(130 reference statements)
2
80
0
1
Order By: Relevance
“…Studies indicate that calls for collective action are reoccurring themes in consumer discourses on sustainable tourism mobility (Higham et al, 2014;Miller et al, 2010). As far we know, only one study considered collective efficacy (as described above) for tourism choices with different environmental implications.…”
Section: Efficacy Beliefsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies indicate that calls for collective action are reoccurring themes in consumer discourses on sustainable tourism mobility (Higham et al, 2014;Miller et al, 2010). As far we know, only one study considered collective efficacy (as described above) for tourism choices with different environmental implications.…”
Section: Efficacy Beliefsmentioning
confidence: 99%
“…On the other hand, if everybody avoids taking environmental issues into account when flying, there is an opportunity cost to this in that global greenhouse gas emissions continue to grow, accumulating to potentially negative consequences for all members of society including oneself. This exemplifies some of the tensions that can arise when private and collective interests are considered in the tourism domain; a phenomenon that has been discussed particularly in regard to air travel decisions and climate concerns (Higham, Cohen, & Cavaliere, 2014). This paper is located within work on the psychological characteristics of those willing to take environmental issues into account when choosing among different tourism alternatives (e.g.…”
Section: Introductionmentioning
confidence: 98%
“…Flying decisions have been selected for two main reasons: firstly, they are notoriously contentious for green consumers and resistant to change (Higham, Cohen, & Cavaliere, 2014); and secondly, because while they are decisions accessible to a wide range of individuals, they are not high frequency, habitual decisions for most. Thus by asking individuals to discuss their decisions to fly or not to fly we expect to find narratives located within the attitude-behaviour gap.…”
Section: Changing Attitudes or Cognitions About Attitudesmentioning
confidence: 99%
“…A body of literature continues to grow around expressed concerns with the contribution that air travel has on CO 2 emissions and climate change (Becken, 2007;Brand & Boardman, 2008;Gössling & Upham, 2009;Hares, Dickinson, & Wilkes, 2010). Simultaneously literature grows around consumer awareness of climate change issues (Higham & Cohen, 2011;KhooLattimore & Prideaux, 2013) and the fact that there are few signs of behaviour change amongst even the most environmentally aware travellers (Barr, Shaw, Coles & Prillwitz, 2010;Higham et al, 2014). In fact, both Barr et al (2010) and Böhler, Grischkat, Haustein, and Hunecke (2006) found that the greenest individuals were the most frequent long-haul (air) travellers.…”
Section: Changing Attitudes or Cognitions About Attitudesmentioning
confidence: 99%
See 1 more Smart Citation